High resolution ultrasonography in isolated soft tissue and intramuscular cysticercosis - Sharma, Gaurav; Ghode, Rita (International Journal of Research in Medical Sciences, 2016)
Background: Cysticercosis is a common parasitic public health issue especially in developing countries. Though the extraneural tissues are usually involved synchronously or metachronously with the brain, isolated infestation of soft tissue and muscle in the absence of neural involvement is more common than previously thought. High resolution ultrasonography has evolved now as an investigation of choice with proven sonological patterns of soft tissue cysticercosis which can entirely negate the need for invasive interventions. The aim of the study is to: a) evaluate the diagnostic utility of HRUSG in isolated soft tissue- intramuscular cysticercosis; and b) evaluate and emphasized the role of the non-surgical conservative medical management in these cases. Methods: Prospective evaluation of total 15 cases of extraneural cysticercosis over a period of 2 years at DMIMS Sawangi. HRUSG analysis of 15 cases was done to evaluate and classify the various classic sonomorphological features of isolated cysticercosis involving soft tissue and muscles. FNAC was done in 3 cases. 12 out of 15 patients were followed up closely over serial ultrasound after initiation of medical therapy at 15 days, 1 month and at 3 months interval. Tablet Albendazole with or without steroid cover was given to each of 12 patients and treatment response was recorded. Results: Out of 15 cases, 7 were male and 8 were female patients. Nine individuals were vegetarian and six were non vegetarian. Mean age was 28 years. All cases were diagnosed on HRUSG. Intramuscular lesion was identified in 11 cases and 4 cases had subcutaneous involvement with anterior abdominal wall in muscular plane as the commonest site in three patients. FNAC was done in 3 cases confirming the cysticercosis and was treated surgically. 12 patients were treated with medical therapy and showed complete resolution at 3 month ultrasound follow up. Conclusions: With the advent of high resolution ultrasonography and increased clinical awareness of the isolated soft tissue-intramuscular cysticercosis especially in endemic zone, a more conservative non-invasive approach can be applied both in diagnosis and treatment of these isolated cases of cysticercosis.